Paternal family history of premature atherosclerotic disease and perinatal death: A population-based cohort study. - Shwe Sin Win; Kari Klungsøyr; Grace M Egeland; Gerhard Sulo (PLoS ONE)
Background Studies have reported that pregnancies conceived by fathers with modifiable cardiovascular risk factors are at higher risk of ending in losses compared to those without such risk factors. Our objective was to examine the association between paternal family history _a non-modifiable risk factor_ of premature atherosclerotic disease and perinatal death. Methods This is a population-based cohort study. Information on fathers, aged 18-50 years who participated in three population-based health surveys conducted in Norway during 1974-2003 was linked to their singleton births registered in the Medical Birth Registry of Norway. We used multilevel mixed effect logistic regression analyses with random intercepts by father's identification number. The birth was the observation unit in all analyses. Results A total of 220,386 fathers who had 512,111 births with information on family history of CHD (12.3% with positive family history) and 203,257 births with information on family history of stroke (9.2% with positive family history) were analysed. There were 782 (1.3%) and 195 (1%) perinatal deaths in births to fathers with family history of CHD and stroke while 5,922 (1.3%) and 1,858 (1%) in those without family histories. We found no association between family history of CHD and stillbirth (OR 1.01, 95% CI 0.92; 1.12), neonatal death (OR 0.98, 95%CI 0.86, 1.11) or perinatal death (OR 1.00, 95% CI 0.92, 1.08). Similarly, we found no associations between family history of stroke and stillbirth (OR 1.00, 95% CI 0.82, 1.21), neonatal death (OR 1.09, 95%CI 0.84, 1.41) or perinatal death (OR 1.02, 95% CI 0.88, 1.20). Limitations Socioeconomic background of fathers was captured using imperfect proxy. Potential misclassification of family history and selection bias should be considered. Conclusion Results of this large, cohort study including half-a million births, do not indicate an association between paternal family history of premature atherosclerotic disease and perinatal death.